Clinicopathological characteristics and outcomes of anti-neutrophil cytoplasmic autoantibody-related renal vasculitis with hyperuricemia: a retrospective case-control study - Ruiqiang Wang (Nature Portfolio, 2021)
Abstract The objective of the study was to evaluate the clinicopathological characteristics and investigate the clinical determinants of patient and renal survival in the first 12 months after diagnosis in anti-neutrophil cytoplasmic antibody (ANCA)-associated renal vasculitis (AAV) patients with hyperuricemia. This was a retrospective case-control study in patients with AAV-related renal injury in the First Affiliated Hospital of Zhengzhou University from January 2014 to April 2019. Patients who met the study criteria were divided into two groups: patients without hyperuricemia (n = 92) and patients with hyperuricemia (n = 55). Participants were followed-up for 12 months, and progressing to end-stage renal disease (ESRD) and death was treated as the endpoint event. We found that the level of serum creatinine was an independent risk factor for hyperuricemia, and the level of serum uric acid was an independent risk factors for renal survival and patient survival in ANCA-associated renal vasculitis patients. The crescents formation and the proportion of fibrous crescent likely contributed to severe clinical characteristics and renal pathological changes in ANCA-associated renal vasculitis patients with hyperuricemia. Hyperuricemia has an important influence on the progression of ANCA-associated renal vasculitis. A good control of serum uric acid may improve the prognosis.